1999
DOI: 10.1021/bc990066n
|View full text |Cite
|
Sign up to set email alerts
|

Folate Copolymer-Mediated Transfection of Cultured Cells

Abstract: Poly(ethylene glycol) of various sizes was used as a molecular spacer to separate the cell-targeting ligand, folate, from the surface of poly-L-lysine. The resulting ternary macromolecule (pLys-PEG-folate) was investigated in various formulations for its ability to transfect reporter plasmids into receptor-bearing HeLa and IGROV cell lines. Formulations were optimized with respect to DNA content, +/- charge ratio, and the size and amount of PEG substitution off the pLys backbone. Transfection activity was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…Flow Cytometry Analysis 293T and 293T-Syn2 cells (6ϫ10 5 ) were treated with anti-syndecan-2 antibody (R&D Systems Inc., Minneapolis, U.S.A.) or isotype control antibody (Bechman Coulter, Inc., Brea, CA, U.S.A.) for 30 min at 4°C. Cells were subsequently treated with Alexa Fluor 488-conjugated secondary antibody (Invitrogen Japan K.K., Tokyo, Japan) for 30 min at 4°C, and then the fluorescence intensities were measured by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow Cytometry Analysis 293T and 293T-Syn2 cells (6ϫ10 5 ) were treated with anti-syndecan-2 antibody (R&D Systems Inc., Minneapolis, U.S.A.) or isotype control antibody (Bechman Coulter, Inc., Brea, CA, U.S.A.) for 30 min at 4°C. Cells were subsequently treated with Alexa Fluor 488-conjugated secondary antibody (Invitrogen Japan K.K., Tokyo, Japan) for 30 min at 4°C, and then the fluorescence intensities were measured by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection of pDNA into Cells Using AG73-PEG Liposomes The 2 d before the experiments, 293T and 293T-Syn2 cells (1ϫ10 5 ) were seeded in a 48-well plate. The cells were treated with AG73-PEG liposomes (pDNA: 0.9 mg/ well) in serum-free medium for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the previous reports demonstrated that an introduction of PEG as a spacer between FA and carriers increases FR-dependent gene transfer activity of liposomes 32 and poly-L-lysine. 33 To improve the FR-binding activity of Fol-a-CDE (G3), therefore, we prepared FolPaCs (G3), which have a PEG spacer between dendrimer and FA ( Figure 1), and examined FR-selective gene transfer activity of FolPaCs (G3, DSF 2, 5 or 7) in KB cells and A549 cells (Figure 3). In KB cells, Fol-PaC (G3, DSF 5) showed a higher gene transfer activity than a-CDE (G3) and Fol-PaCs (G3, DSF 2 and 7) (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that z-potential values of the pDNA complex with Fol-PaC (G3, DSF 5) at a charge ratio of 50 were close to neutral, compared with that of a-CDE (G3), because of an introduction of Fol-PEG moieties to dendrimer molecule. Leamon et al 33 reported that a neutral complex is desirable to incorporate into a ligand-targeted gene transfer carrier because it eliminates the opportunity for the non-specific adsorptive binding to non-target cells. Reddy et al 39,40 demonstrated that folate-linked carriers of diameters o150 nm are efficiently bound and internalized by FR-expressing cells.…”
Section: Dendrimer -Cde (G3)mentioning
confidence: 99%